Respuesta :
Answer:
a) v = 3.57 m/s
b) N = 2.59 W
Explanation:
a) Maximum height, h = 65 cm = 0.65 m
The speed of the person at which he leaves the ground can be calculated by the equation of motion:
[tex]v^{2} = u^{2} + 2gh[/tex]
u = 0 m/s
[tex]v^{2} = 0 + 2gh\\v^{2} = 2gh\\v^{2} = 2 * 9.8 * 0.65\\v^{2} = 12.74\\v = 3.57 m/s[/tex]
b)
The displacement of the person when he jumps, S = 41 cm = 0.41 m
To calculate the acceleration of the person:
[tex]v^{2} = u^{2} + 2aS\\u = 0 m/s\\v^{2} = 2aS\\3.57^{2} = 2 * a * 0.41\\12.74 = 0.82 a\\a = 12.74/0.82\\a = 15.54 m / s^2[/tex]
The force exerted by the person can be given as:
F = N - mg
N = Normal reaction ( the ground's force on him)
mg = W ( Weight of the person)
F = ma
ma = N - mg
Divide through by mg
[tex]\frac{ma}{mg} = \frac{N}{mg} - \frac{mg}{mg} \\\frac{a}{g} = \frac{N}{mg} - 1\\ W = mg\\\frac{a}{g} + 1= \frac{N}{W}\\\frac{15.54}{9.8} + 1 = \frac{N}{W}\\2.59 = \frac{N}{W}\\N = 2.59W[/tex]
Answer:
Explanation:
We can approach this question from Newton's Law of Motion.
The first law states that an object will continue moving on a straight line until an external force is acted upon it . Now from the classical mechanics perspective ; if the net force on an object happens to be zero, the body of such object typically implies to be at rest.
The second law of motion states that , the acceleration of an object is directly proportional to the force acting upon it but inversely proportional to the mass.
So; mathematically; we can have:
[tex]\sum F = ma[/tex]
Newton third law of motion states that for every action , there is equal but an opposite reaction.
A
From the question;
The initial speed [tex]v_i =[/tex]0
But the final speed can be determined by the using he following relation:
[tex]v_f^2 = v_i^2 +2a \Delta x \\ \\ v_f^2 = 0+2g \Delta x \\ \\ v_f^2 =2g \Delta x \\ \\ v_f^2 = 2*9.8*0.65 \\ \\ v_f^2 = 12.74m^2/s^2 \\ \\ v_f= \sqrt{12.74m^2/s^2} \\ \\ v_f= 3.569 \ m/s[/tex]
B
To calculate the acceleration of the of the jumper ; we use the relation;
[tex]v_f^2 = v_i^2 +2a \Delta x \\ \\ v_f^2 = 0+2a \Delta x \\ \\ v_f^2 =2a \Delta x \\ \\ a= \dfrac{v_f^2}{2 \Delta x}[/tex]
[tex]a= \dfrac{12.74}{2*0.41}[/tex]
a = 15.533 m/s²
[tex]\sum F = ma\\ \\ F- W[/tex]
By rearrangement and solving for F; we have:
F = ma + W
F = ma + mg
F = m(a+ g)
F = w/g (a+g)
F = w/9.8 m/s² ( 15.533 + 9.8)m/s²
F = w/9.8 m/s² (25.333)m/s²
F = 2.585 w